Students Characteristics in Higher Educational Institution according to the Identities of Catholic Education. - Chuenboon, Dr.Athcha; Saengdararat, Dr.Chutima; Kitcharoen, Rev.Asst.Prof.Dr.Aphisit; Phongprasertsin, Saranyu; Sitthi-amorn, Professor Emeritus Chitr (Saengtham College Journal, 2020)
The purposes of this descriptive research aimed to 1) study the students characteristics in higher educational institution according to the identities of Catholic Education and 2) compare the students characteristics in higher educational institution according to the identities of Catholic Education by their class level and field of study 3) The sample group used in this study were the 1,111 undergraduate students in Catholic higher education institutions in Thailand. There were five public institutes supervised by the Higher Education Commission, The Ministry of Education. The sample was collected using multi-stage sampling method while the tool used for identifying the characteristics of students was a 10-levels rating scale questionnaire. The questionnaire had 0.97 reliability. Analyzing descriptive statistics and analysis of variance, the result were shown as follow. 1. Students characteristics in higher educational institution according to the Identities of Catholic Education was rated at a high level. 2. Class level and field of study in differences were affected the students characteristics in higher educational institution according to the identities of Catholic Education at 0.05 significant level.